Peran Pengasuh Panti Asuhan dalam Membina Disiplin Diri Anak-Anak Panti Asuhan Muhammadiyah Cab Guguak II - Sri Astuti Eka Putri; Alfi Rahmi; Jhon Erita (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The problem in this research is that there are some orphanage children who have not shown good self discipline, where the orphanage children do not wake up on time, pray, and spend a lot of time playing on cellphones annot enough time studying. The aim of this research is to describe the role of caregivers in fostering self discipline in orphanage children. The research method used is a qualitative approach with a descriptive type. The first informant of this research was the caretaker of the orphanage and the supporting informants were the children of the Muhammadiyah Cab Guguak II orphanage. The data collection techniques used were interviews, observation and documentation. The results og the research show that the role of caragivers in fostering self discipline in orphanage children who are not discipline. The aims to ensure that the orphanage children become independent, firm and successful individuals. In the future, as well as giving praise to the`orphanage children who have been able to discipline themselves well, this aims to ensure that the orphanage children can maintain and improve their good self discipline with the role of caregivers like that it can make the orphanage’s children are comfortable and successin their future and can make the people around them proud.